Mobilizing Putrajawa Village Towards Zero New Stunting Through Educational and Awareness Seminars - Suwandi, Deden Winda; Herlina, Lina; bhila, Nayla Shalsa; Salsabila, Hanum; Sapta, Agis; S. Rezeqi, Kayla; Aulia, Nita (Fakultas Kewirausahaan Universitas Garut, 2024)
The problem of stunting in Indonesia is a challenge faced in almost all regions, including Garut Regency. To overcome the problem of stunting incidence in Garut Regency, a community service program was implemented in Putrajawa Village, Selaawi District. This program aims to reduce stunting rates through educational seminars designed to increase awareness and understanding of pregnant women and mothers of children under 0-24 months about the causes, impacts, and prevention strategies of stunting. The method used was a one-group pre-test and post-test design, which was used to evaluate changes in participants' knowledge before and after the intervention. The results of the seminar showed a significant increase in participants' understanding of stunting and its prevention measures, with the percentage of good knowledge increasing from 78% before the seminar to 94% after the seminar.